Sexism at the Bar and the Equitable Briefing Policy:A Well-Meaning but Misguided Response to Gendered Briefing Practices - Ryan Chan (Bond Law Review, 2017)
This article considers a recent regulatory initiative formulated by the Law Council of Australia called theEquitable Briefing Policy (‘EBP’), which aims to address the disadvantage experienced by female practitionersat the Australian Bar. This article examines the origins and underlying rationales of the Policy. It contends thatthe Policy’s potential in deinstitutionalising gendered briefing practices at the Australian Bar is inhibited byAustralia’s policymaking avoidance towards any form of ‘affirmative action’. This aversion is due to theconventional understanding that affirmative action and the merit principle are positioned in a dichotomousrelationship, and thus remain inherently in tension with one another. It is argued, however, that in the contextof briefing practices in Australia, such an understanding is primitive, and using merit as a means of rejectingother policy approaches only serves to inhibit the Policy’s application and effect.